Best Ever Mission Stories B.2 - Ishkanian, Charlotte; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2009)
Provides examples of many ordinary young people who dare to do extraordinary things for God and others.
Keywords: Adult Nonfiction